The Colonization History of Juniperus brevifolia (Cupressaceae) in the Azores Islands - Rumeu, Beatriz (2011)
BACKGROUND: A central aim of island biogeography is to understand the colonization history of insular species using current distributions, fossil records and genetic diversity. Here, we analyze five plastid DNA regions of the endangered Juniperus brevifolia, which is endemic to the Azores archipelago. METHODOLOGY/PRINCIPAL FINDINGS: The phylogeny of the section Juniperus and the phylogeographic analyses of J. brevifolia based on the coalescence theory of allele (plastid) diversity suggest that: (1) a single introduction event likely occurred from Europe; (2) genetic diversification and inter-island dispersal postdated the emergence of the oldest island (Santa Maria, 8.12 Ma); (3) the genetic differentiation found in populations on the islands with higher age and smaller distance to the continent is significantly higher than that on the younger, more remote ones; (4) the high number of haplotypes observed (16), and the widespread distribution of the most frequent and ancestral ones across the archipelago, are indicating early diversification, demographic expansion, and recurrent dispersal. In contrast, restriction of six of the seven derived haplotypes to single islands is construed as reflecting significant isolation time prior to colonization. CONCLUSIONS/SIGNIFICANCE: Our phylogeographic reconstruction points to the sequence of island emergence as the key factor to explain the distribution of plastid DNA variation. The reproductive traits of this juniper species (anemophily, ornithochory, multi-seeded cones), together with its broad ecological range, appear to be largely responsible for recurrent inter-island colonization of ancestral haplotypes. In contrast, certain delay in colonization of new haplotypes may reflect intraspecific habitat competition on islands where this juniper was already present.